The effect of E-commerce on digital inclusive finance: evidence from the E-commerce boom in rural China - Yi-Fan Zhang; Haoxing Zhao (Cogent Economics & Finance)
Digital inclusive finance is an important means for China to improve the financial inclusion rate and promote common prosperity. Rural development issues are related to China’s social stability and national strength, and they are also key issues in the process of building a moderately prosperous society in all respects. Since the 2010s, China has initiated pilot policies for rural e-commerce. As a crucial policy for rural revitalization and rural economic development, whether the e-commerce to rural areas policy can drive the development of digital inclusive finance in Chinese rural areas deserves significant attention. This paper delves into the impact of this policy on digital inclusive finance in rural areas. Based on quasi-natural experiment data including 2844 counties in China, we employ a staggered difference-in-differences (DiD) model and find that after the arrival of the e-commerce boom, the digital inclusive finance index increased largely. Further mechanism analysis shows that this policy facilitated faster growth in farmers’ income, improved their consumption structure, and promoted innovation in rural areas. Moreover, the policy significantly enhanced digital inclusive finance in larger cities and cities with more developed digital infrastructure. Our manuscript can help the Chinese government optimize relevant policies and reveal the importance of e-commerce in rural development.